2013
DOI: 10.4034/rbcs.2013.17.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Perfil das Internações de Crianças e Adolescentes com Fraturas do Crânio e Ossos da Face na Região Nordeste do Brasil

Abstract: RESUMOObjetivo: Analisar o perfil das internações de crianças e adolescentes com fraturas do crânio e ossos da face na região Nordeste, Brasil, no período de 2008 a 2010. Material e Métodos: Utilizou-se uma abordagem indutiva com procedimento comparativo-descritivo e técnica de documentação indireta. Os dados foram obtidos mediante consulta aos sítios do DATASUS para os anos de 2008 a 2010, nas faixas etárias de 0 a 19 anos, considerando as informações disponíveis para cada estado da região nordeste, sendo ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
1
2
0
7
Order By: Relevance
“…It was observed that the hospitalization rate rises with increasing age, being more significant in this study in the age group 15-19 years, being in line with other national [8,9,13,29] and international 30 studies. These findings cause concern, both from the financial point of view and from the perspective of rehabilitation of these patients due to the severity of fractures, which can lead to irreversible consequences, as well as the slower process of bone and tissue repair when compared with regeneration and osteosynthesis in children [11].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…It was observed that the hospitalization rate rises with increasing age, being more significant in this study in the age group 15-19 years, being in line with other national [8,9,13,29] and international 30 studies. These findings cause concern, both from the financial point of view and from the perspective of rehabilitation of these patients due to the severity of fractures, which can lead to irreversible consequences, as well as the slower process of bone and tissue repair when compared with regeneration and osteosynthesis in children [11].…”
Section: Resultssupporting
confidence: 75%
“…Compared to younger children, even in the face of cultural changes, it was observed that girls show greater involvement in group activities or restricted to toys and hand games, which make them less exposed to situations and / or risk for the occurrence of fractures, the latter being more common among male children [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No caso das crianças de 1 a 3 anos, por estar em fase de maturação motora, cognitiva e psicossocial, estão aprendendo a conhecer os seus limites e adaptando-se ao meio. Para crianças acima de 4 anos podem ser pertinentes atividades de lazer e de esporte próprios da idade (16,18) , somados ainda ao aumento do peso, de altura, de força e de agressividade após os 5 anos de idade, promovendo a ocorrência e a gravidade dos traumas (19) . Neste contexto, percebe-se que a queda na infância é concebida como acontecimento normal do cotidiano infantil.…”
Section: Discussionunclassified
“…A utilização do serviço público pode ser guiada por diferentes perfis de atendimento, seja ele pautado em métodos preventivos a serem realizados na atenção básica, em métodos curativistas, e até mesmo na utilização como porta de entrada para consultas especializadas, como as ofertadas nos Centros de Especialidades Odontológicas (CEOs) 6,22 .…”
Section: Tabela 3 Médias Populacionais Das Regiões Brasileirasunclassified